The effectiveness of natural probiotics in food - Urbaś, Michał; Kościołek, Dawid; Kępczyk, Martyna; Kościołek, Aleksandra; Surowiecka, Kaja; Misiak, Jakub; Ojdana, Miłosz; Szalbot, Konrad; Tokarski, Mikołaj; Czchowski, Konrad (Journal of Education, Health and Sport, 2024)
Introduction and purpose The term "probiotic" rooted in Latin, signifies ’for life,’ reflecting the historical use of fermented products for therapeutic purposes. Defined by the WHO as living microorganisms conferring health benefits when consumed adequately, probiotics, mainly bacteria from Lactobacillus and Bifidobacterium genera, play a vital role in maintaining gut microbiota balance, regulating digestion, supporting the immune system and influencing mental and cardiovascular health. While browsing many websites devoted to healthy eating or popular science topics, we often came across the topic of probiotic food without any confirmation by scientific research. The aim of this paper is to confirm or exclude the presence of probiotics in popular foods. Material and method In our work, we will look at individual products with an emphasis on verifying whether the microorganisms they contain meet the WHO criteria of probiotics. Results Our review managed to prove the probiotic effect of almost all presented food, except for miso. By reviewing many articles, we shed a lot of uncertainty on the repeated myth about the lack of probiotic effect of cucumbers preserved in vinegar and what is more, we found scientific assumptions about the probiotic effect of vinegar itself. Conclusion Fermented food contains numerous strains of bacteria that are resistant to acid, bile and temperature in the human digestive tract and can be effectively used as a source of probiotics. What is more, compared with probiotics from the pharmacy, pickles provide not only probiotics, but also nutritional values, valuable fiber and vitamins. They seem to be a versatile supplement for our health.